Study of the Rocks and Analysis of Morphotectonic Uplift Between Kirkuk and Qara Chauq Anticlines Using Remote Sensing Techniques - Hamdon, Alaa N.; Ibraheem, Laith kh.; Hussain, Ghazi A. (Iraqi Journal of Science, 2020)
This study aims to demonstrate the morphotectonic evidence (drainage pattern, formations of sedimentary rocks, structural ridge deformations and spectral reflectance differences…etc.) for tectonic uplift with the syncline zone between two major anticlines, Kirkuk anticline in the northeast and Qara Chauq anticline in the southwest. The study area is located in the low folded zone at the geographical coordinates of 35º 45´ to 35º 55´ North and 43º 30´ to 44º 00´ East. In this study, the tectonic uplift was named as Dushwan uplift, because the uplift of the rocks was adjacent to Dushwan village. The regional stress, originating from the collision of the Arabian plate with the Eurasian plate, is still affecting the study area, as presented by the rock deformations of the southwestern structural ridges of Kirkuk anticline and the whole Qara Chauq structure. It is dividing the drainage pattern basin within the major syncline into two different drainage basins with different directions from the center of this uplift, in addition to the rocks deformation of the eastern plunge of Bai Hassan anticline. This uplift was demonstrated through four sectional profiles made by using Google Earth and Global Mapper software. In addition, the uplift of the rocks was identified by the visual interpretation of the satellite images and the digital interpretation of the DEM and satellite images using software (such as Arc GIS and Global Mapper) for the study area. The above morphotectonic evidence indicate that the rocks in the study area are influenced by tectonic activity (Dushwan uplift) through three suggested mechanisms; First, propagation of two synclines, one existed between Kirkuk anticline and Bai Hassan Anticline and the other located between Qara Chauq anticline and Guwair anticline of a northwest- southeast trend. Second, this uplift of the rocks was resulted by a deep-seated fault that extends to the basement faults with a northeast- southwest direction. Third, a Salt Diapir was forced from salty formations existed in this area.